Improving the Safety of Opioid Use for Acute Noncancer Pain in Hospitalized Adults: A Consensus Statement From the Society of Hospital Medicine. Issue 4 (1st April 2018) - Herzig, Shoshana J.; Mosher, Hilary J.; Calcaterra, Susan L.; Jena, Anupam B.; Nuckols, Teryl K.
Abstract : Hospital‐based clinicians frequently treat acute, noncancer pain. Although opioids may be beneficial in this setting, the benefits must be balanced with the risks of adverse events, including inadvertent overdose and prolonged opioid use, physical dependence, or development of opioid use disorder. In an era of epidemic opioid use and related harms, the Society of Hospital Medicine (SHM) convened a working group to develop a consensus statement on opioid use for adults hospitalized with acute, noncancer pain, outside of the palliative, end‐of‐life, and intensive care settings. The guidance is intended for clinicians practicing medicine in the inpatient setting (eg, hospitalists, primary care physicians, family physicians, nurse practitioners, and physician assistants). To develop the Consensus Statement, the working group conducted a systematic review of relevant guidelines, composed a draft Statement based on extracted recommendations, and obtained feedback from external experts in hospital‐based opioid prescribing, SHM members, the SHM Patient‐Family Advisory Council, other professional societies, and peer‐reviewers. The iterative development process resulted in a final Consensus Statement consisting of 16 recommendations covering 1) whether to use opioids in the hospital, 2) how to improve the safety of opioid use during hospitalization, and 3) how to improve the safety of opioid prescribing at hospital discharge. As most guideline recommendations from which the Consensus Statement was derived were based on expert opinion alone, the working group identified key issues for future research to support evidence‐based practice.